Les conceptions en matière de sécularisation de la science et de la société vont-elles ou non de pair ? Enquête réalisée en Belgique et au Maroc auprès d’élèves de terminale - José-Luis Wolfs (Recherches en Éducation)
To what extent does the adherence to a secularized conception of science of an individual depend on his conceptions of secularization in other fields (politics, ethic, society)? To what extent are the different dimensions linked or not? This question, already raised by Weber, is examined here on the basis of an exploratory survey carried out in two countries with contrasting conceptions of secularisation (Belgium and Morocco): 196 Muslim Moroccan pupils and 621 Muslims, Catholics and agnostics or atheists pupils from Belgium were asked by a closed-response questionnaire about their views on the secularization of both science and society. This inquiry with questions the concept of secularization on the theoretical and empirical plans leads to an observation and new questions. It appears that students with a secularized conception of science almost all have secularized conception on societal aspects, but the reverse is not true. The role of several variables related to the societal context of these two countries and the religious affiliation of the pupils is analysed.